SURFACE CHARACTERISTICS OF STAINLESS STEEL AISI 3 I 6L AFTER LOW TEMPERATURE HYBRID THERMOCHEMICAL TREATMENT - BRONTO AGUNG, ASKAR TRIWIY ANTO (2013)
Austenitic stainless steels are the most popular materials in the stainless steel family used in various applications due to their excellent corrosion resistance and good Conning characteristics. Nevertheless. this type of materials has low hardness as well as poor wear resistance due to the inherent austenitic structure. Earlier attempts to increase the surface hardness and wear resistance of austenitic stainless steels b) surface treatments have led to the deterioration in corrosion resistance arising from the depletion in chromium in the hardened layer. The development of low temperature nitriding and carburizing processes which are carried out at temperatures lower than 500°C without impairing its corrosion resistance have been successfully conducted by innovative techniques. including plasma nitriding. ion beam nitriding and ion implantation.